(untitled) (Sebha University Conference Proceedings, 2024)
Flowable Fill Materials (FFM) are commonly known as cementitious materials that are low shrinkage, self-compacting and self-leveling. FFM are generally employed to substitute backfill soil and traditional construction fillings. This paper produces the outcomes of experimental study that has intention to examine incorporation demolishing waste materials in production flowable fill materials. the experimental work was separated into two parts, first part investigates the pozzolanic activity for different demolishing waste materials (glass, clay bricks, and Autoclaved Aerated Concrete blocks). Six different mixes of demolishing waste powder were tested by pozzolanic activity index test. The second part used an optimal pozzolanic demolishing waste for producing FFM. Ten mixes of FFM containing the optimal demolishing waste material ranged from 5% to 20% as cement replacement were prepared. Then the basic properties of FFM like flowability , unconfined compressive strength at different age , density were examined. Overall, the outcomes illustrate that demolishing waste materials especially glass powder can effectively utilize as cement replacement in flowable fill application.